Pengetahuan dan sikap petugas kesehatan di pelayanan kesehatan primer dalam tata laksana kekerasan terhadap anak - Meita Dhamayanti; Insa Farisa Desy Arya; Raina Syah Fanissa (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2019)
Child abuse is a serious problem. Child abuse victims should get standarized management unless so it will affect the quality of life of the children in the future. Health services for child abuse victim are carried out through basic level services, namely the “puskesmas”. This study aims to determine the knowledge, attitudes, and behavior of health workers in primary health care on management of child abuse victims. The descriptive cross sectional study by using a questionnaires to health workers who work in Puskesmas Ramah Anak in the Bandung City. The data of gender, profession, length of time working at the Puskesmas Ramah Anak, recent education, experience in training management of violence against children, level of knowledge, attitudes, and behavior in the management of child sexual abuse. The questionnaire was distributed to 69 respondents and only 56 respondents entered the inclusion criteria. All of respondents have good knowledge 55.0% have a positive attitude and 54.0% ever done management of child sexual abuse. Health workers at the puskesmas in Bandung City generally have good knowledge of child sexual abuse management and agreeing that the management of child abuse must be carried out properly and also managed child sexual abuse in accordance with the guidelines provided.